At home on the street: people, poverty and a hidden culture of homelessness - Wasserman, Jason Adam (Lynne Rienner Publishers)
Introduction: homelessness in the United States -- Accessing a hidden population -- Describing those who are homeless -- Causes of homelessness -- Urban space and relations on the street -- The complex dispositions of those on the street -- Street identities and creative resistance -- Business, politics, and the moving ghetto -- Homeless services: healing the sick -- Religious approaches: saving souls -- Conclusion: improving research, improving policy